Pengaruh Tekanan Ketaatan, Kompleksitas Tugas,Pengetahuan Dan Pengalaman Auditor Terhadapaudit Judgement(Studi Kasus Pada BPK Perwakilan JawaTengah) - Ratna Dewi, Fauzia, Drs. Suyatmin Waskito Adi, M.Si (2017)
Auditor is a professional whose job carrying out an audit of the entity's financial statements and draw conclusions. Audit judgement a significant influence on final conclusion, so that will affect the opinion will be issued by the auditor. Research objective to determine the effect of presure obedience, complexity of the task, knowledge, and audit experience influence on audit judgement. The population in this research are auditors who work on Badan Pemeriksa Keuangan (BPK) Representative of Central Java Province. The sampling method in this research using convenience sampling method and the amount of samples as much as 35.The data were obtained using a questionare technique. methods of data analysis used was Multiple Linier Regression analysis. The result of this research showed that presure obedience, complexity of the task knowledge affectaudit judgment,but audit experience didn't affect audit judgment.